THE EFFECT OF OWNERSHIP STRUCTURE, PROFITABILITY, AND FIRM SIZE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Dea Yovita Purnomo; Ari Prasetyo (Universitas Airlangga, 2021)
ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh Struktur Kepemilikan, Profitabilitas dan Ukuran Perusahaan terhadap Corporate Social Responsibility. Teknik analisis yang dipilih merupakan analisis regresi data panel menggunakan Eviews 9, pada 13 perusahaan yang terdaftar dalam Jakarta Islamic Index (JII) tahun 2015-2019 sebagai sampel dengan kriteria tertentu. Variabel struktur kepemilikan dibagi menjadi kepemilikan domestik dan asing yang diukur dengan presentase kepemilikan saham di perusahaan, profitabilitas dihitung dengan ROA, ukuran perusahaan diukur dengan ln (logaritma natural) total aset dan pengungkapan CSR dihitung menggunakan ISR dengan cara presentase pengungkapan perusahaan dibagi dengan jumlah maksimum pengungkapan tanggung jawab sosial. Hasil olah data menemukan secara statistik kepemilikan domestik memiliki hubungan negatif signifikan terhadap pengungkapan CSR. Ukuran perusahaan secara statistik memiliki hubungan positif signifikan terhadap pengungkapan CSR. Sebaliknya profitabilitas dan kepemilikan asing secara statistik memiliki hubungan positif tidak signifikan terhadap pengungkapan CSR. Secara simultan, hasil olah data menunjukkan bahwa struktur kepemilikan yang dibagi menjadi kepemilikan domestik dan asing, profitabilitas dan ukuran perusahaan berpengaruh terhadap pengungkapan CSR pada 13 perusahaan yang terdaftar di JII tahun 2015-2019.Kata Kunci: Pengungkapan Corporate Social Responsibility, Ukuran Perusahaan, Islamic Social Reporting, Kepemilikan Asing, Kepemilikan Domestik, Pofitabilitas, Struktur Kepemilikan. ABSTRACTThe purpose of this study is to examine the effect of ownership structure, profitability, and firm size on corporate social responsibility. The analysis technique chosen is panel data regression analysis using Eviews 9, on 13 companies listed in the Jakarta Islamic Index (JII) 2015-2019 as samples with certain criteria. The variable of ownership structure divided into domestic and foreign ownership calculated using percentage of share ownership in the company, profitability is calculated by ROA, company size is calculated using ln (natural logarithm) total assets and CSR disclosure is calculated using ISR index by percentage of company disclosures divided by the number of social responsibility disclosures. The results of data processing found that statistically domestic ownership has a significant negative relationship to CSR disclosure. Firm size has a statistically significant positive relationship to CSR disclosure. On the other hand, profitability and foreign ownership have a statistically insignificant positive towards CSR disclosure. Simultaneously, the results show the ownership structure divided by domestic and foreign ownership, profitability and company size affects the CSR disclosure in 13 companies listed in JII 2015-2019.Keywords: Corporate Social Responsibility Disclosure, Islamic Social Reporting, Ownership Structure, Domestik Ownership, Foreign Ownership, Profitability, Company Size.DAFTAR PUSTAKAAkbar, D. (2017). Investigation of intellectual capital impact and firm size to islamic social reporting with profitability as mediation on sharia banks in Indonesia. Man in India, 97(24), 413–438.Amran, A. (2008). The impact of government and foreign affiliate influence on corporate social reporting: The case of Malaysia. Managerial Auditing Journal, 23(4), 386–404.Astuti, T. (2013). Pengaruh profitabilitas, likuiditas dan leverage terhadap pengungkapan islamic social reporting (Studi empiris pada perusahaan yang terdaftar di bursa efek Indonesia). Jurnal Universitas Islam Negeri Syarif Hidayatullah Jakarta, 1-20.Cahyani, C., & Suryaningsih, R. (2016). The effect of leverage, board of commissioner, foreign ownership, company age, and company size towards the disclosure of corporate social responsibility (CSR) implementation. Accounting and Finance Review, 1(1), 27–33.Freeman, R. E. (1999). Response: Divergent stakeholder theory. Academy of Management Review, 24(2), 233–236.Haniffa, D. R. M., & Hudaib, D. M. A. (2002). A theoretical framework for the development of the Islamic perspective of accounting. Accounting, Commerce & Finance: The Islamic Perspective Journal, 6, 1–71.Hossain, M., Marks, B. R., & Mitra, S. (2006). Stock ownership structure and voluntary disclosure of quarterly foreign sales data of U.S. multinational corporations. The Multinational Business Review, 14(3), 71–94. https://doi.org/10.1108/1525383X200600014Irmadariyani, R., Fadah, I., Tobing, D. S. K., & Wardayati, S. M. (2019). Empirical investigation of the role of Sharia’s corporate social responsibility on the relationship between firm size and profitability. International Journal of Scientific and Technology Research, 8(7), 18–22.Liu, A. M., Irwansyah., & Fakhroni, Z. (2016). Peran agency cost reduction dalam memediasi hubungan antara corporate social responsibility dengan nilai perusahaan. Jurnal Ekonomi, Manajemen dan Akuntansi, 18(2), 141–156.Nohong, M. (2019). Islamic Social Reporting disclosure and firm value: Empirical study of firms listed in Jakarta Islamic Index. Proceedings of the International Conference on Industrial Engineering and Operations Management, 2458–2494.Othman, Rohana., Thani, A. M., & Ghani, E. K. (2009). Determinants of Islamic social reporting among top shariah-approved companies in Bursa Malaysia. Research Journal of International Studies, 12(12), 4–20.Othman, Rohana., & Thani, A. M. (2010). Islamic social reporting of listed companies in Malaysia. International Business & Economics Research Journal (IBER), 9(4), 135–144.Prado-Lorenzo, J. (2009). Stakeholder engagement and corporate social responsibility reporting: The ownership structure effect. Corporate Social Responsibility and Environmental Management, 16(2), 94–107.Putra, W. E., Yuliusman., & Setiawan, D. (2011). Pengaruh size, profitabilitas, leverage, kepemilikan dalam negeri dan kepemilikan asing terhadap pengungkapan tanggung jawab sosial perusahaan. Jurnal Penelitian Universitas Jambi Seri Humaniora, 13(2), 37–48.Said, R., Zainuddin, Y. H., & Haron, H. (2009). The relationship between corporate social responsibility disclosure and corporate governance characteristics in Malaysian public listed companies. Social Responsibility Journal, 5(2), 212–226.Suto, M., & Takehara, H. (2012). Stock ownership structure and corporate social performance: Evidence from Japan. Diakses dari https://studylib.net/doc/6916206/stock-ownership-structure-and-corporate-social-performanceTokas, K. (2020). Foreign ownership and corporate social responsibility: The case of an emerging market. Global Business Review, 1-24. https://doi.org/10.1177/0972150920920444Xu, B. (2016). Profitability, state ownership, tax reporting and corporate social responsibility: Evidence from chinese listed firms. Social Responsibility Journal, 12(1), 23–31.